Analysis of a tapered vane loaded broad-band gyro-TWT - Agrawal M.; Singh G.; Jain P.K.; Basu B.N. (My University, 2025)
In this theoretical paper, the wide-band low-gain feature of a tapered smooth wall gyro-traveling wave tube (gyro-TWT) was combined with the low beam energy, low magnetic field, and high gain, though narrow band, feature of a vane loaded nontapered gyro-TWT, to propose a distributed, tapered vane loaded gyro-TWT, for both high gains and wide bandwidths. The device was analyzed for the tapering of any one of the three parameters-the waveguide radius, the vane depth, and the vane angle-keeping the remaining two as constant. The magnetic field was also synchronously tapered. The optimum taper and vane parameters were predicted for a large gain and bandwidth.